2017
DOI: 10.5430/ijfr.v9n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Monday Effect in the Chinese Stock Market

Abstract: The Monday effect is a well know effect in some countries around the world. The Monday effect is the observation that stock returns on Monday are statically significantly lower than for the rest of the days of the week. There is no obvious fundamental reason behind this occurrence and if it actually exists it might be due to human behavioral patterns. This Monday effect observation originated in the U.S. several decades ago and it has since being observed in several other countries. In this article the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…However, according to Perez (), the Monday effect can be explained by the asset liquidity. Indeed, the role of liquidity on the stock market calendar anomalies has been confirmed by numerous empirical findings.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to Perez (), the Monday effect can be explained by the asset liquidity. Indeed, the role of liquidity on the stock market calendar anomalies has been confirmed by numerous empirical findings.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang and Li (2006) investigated time-varying calendar effects in the Chinese stock markets using GARCH-Generalized Error Distribution (GARCH-GED) model and found that Friday effect disappeared and significant positive returns appeared on Tuesday. Other studies, such as Qiao et al (2011) and Perez (2018), in China also found the existence of day-ofthe-week effect. Soares et al (2013) and Sehgal et al (2014) found the existence of day-of-theweek effects in Brazil using OLS regression and Capital Asset Pricing Model (CAPM).…”
Section: Literature Reviewmentioning
confidence: 67%
“…However, the majority of research papers appear to concentrate around USA and other developed markets (Guidi et al, 2011;Chatzitzisi et al, 2021;Khan and Rabbani, 2019;Plastun et al, 2019). Recently, some of the literature focused on Asian countries (Jaisinghani, 2016;Perez, 2018;Toit et al, 2018). Therefore, calendar anomalies appear to exist not only in developed stock markets, but also in emerging Asian countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasar dikatakan efisien jika investor individu maupun investor institusi tidak dapat memperoleh abnormal return dalam jangka waktu yang panjang dengan menggunakan strategi perdagangan yang ada. Menurut Perez (2018) pasar modal dikatakan tidak efisien jika perusahaan berada dalam situasi yang mempengaruhi operasi bisnisnya dan informasi yang tersedia untuk umum, tetapi tindakan perusahaan tidak mengubah harga pasarnya. Jika hal ini terjadi, maka para investor dapat memanfaatkan fenomena ini dan menyusun strategi agar mendapatkan abnormal return.…”
Section: Pendahuluanunclassified